Electron density distribution in H ii regions in IC 10 - Polles, Fiorella L.; Fadda, Dario; Vacca, William D.; Abel, Nicholas P.; Chevance, Mélanie; Fischer, Christian; Jackson, James M.; Lebouteiller, Vianney; Madden, Suzanne; Ramambason, Lise (The astronomical journal, 2024)
We present the [O III] λ52 μm map of the dwarf galaxy IC 10 obtained with the Field-Imaging Far-Infrared Line Spectrometer on board the Stratospheric Observatory for Infrared Astronomy. We combine the [O III] λ52 μm map with Herschel and Spitzer observations to estimate the electron density distribution of the brightest H ii regions of IC 10. We find that the line ratio [O III] λ88 μm/[O III] λ52 μm gives electron density (n e) values (n e [O III]) that cover a broad range, while the n e values obtained using the line ratio [S III] λ33 μm/[S III] λ18 μm (n e [S III]) are all similar within the uncertainties. n e [O III] is similar to n e [S III] for the M1, M2, and A1 regions, and it is higher than n e [S III] for the two regions, A2 and M1b, which are the brightest in the 24 μm continuum emission. These results suggest that for these regions, the two ions, O++ and S++, trace two different ionized gas components and that the properties of the ionized gas component traced by the O++ ion are more sensitive to the local physical conditions. In fact, while the gas layer traced by [S III] does not keep track of the characteristics of the radiation field, the n e [O III] correlates with the star formation rate, the dust temperature, and the 24 μm. Therefore, n e [O III] is an indicator of the evolutionary stage of the H ii region and the radiation field, with higher n e [O III] found in younger star-forming regions and in more energetic environments.